2017
DOI: 10.1002/adsc.201700168
|View full text |Cite
|
Sign up to set email alerts
|

NBS‐Mediated Oxygen Transfer Reaction of Carbonyl in Ester: Efficient Synthesis of Benzil–o‐carboxylate Derivative From o‐Alkynylbenzoate

Abstract: A neighbouring ester group‐participated diketonization of o‐alkynylbenzoate is described here for the synthesis of benzil‐o‐carboxylate. Application of the resulting benzil‐o‐carboxylate in the synthesis of quinoxalines is also reached from o‐alkynylbenzoate in an one‐pot fashion. This diketonization proceeds smoothly with a high regioselectivity under mild conditions. Importantly, neighbouring group plays an important role in diketonization. A plausible mechanism suggests that a bromo‐incoporated isocoumarin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It has been reported that a carbonyl group in the ortho ‐position of a phenylacetylene moiety can participate in the diketonization , . We observed such a neighbouring group participation when methyl 2‐(phenylethynyl) benzoate ( 1p ) was reacted under the optimized reaction conditions and 3‐phenyl‐1 H ‐isochromen‐1‐one ( 3 ) – and not diketone 2p – was obtained as the major product (Scheme ).…”
Section: Resultsmentioning
confidence: 72%
“…It has been reported that a carbonyl group in the ortho ‐position of a phenylacetylene moiety can participate in the diketonization , . We observed such a neighbouring group participation when methyl 2‐(phenylethynyl) benzoate ( 1p ) was reacted under the optimized reaction conditions and 3‐phenyl‐1 H ‐isochromen‐1‐one ( 3 ) – and not diketone 2p – was obtained as the major product (Scheme ).…”
Section: Resultsmentioning
confidence: 72%
“…This is the first report, where ortho ‐ester‐assisted halogenation of alkynes 184 provides α,α‐dihaloketone 185 without terminating the reaction at isocoumarin 186 or isochromenol stage. Two similar protocols were also developed by the research groups of Qiu and Liu et al., for the oxidative dibromination followed by water addition across the alkyne 184 to generate 1,2‐diketones 185 (Scheme ). Tetrabutylammonium bromide (TBAB) and oxone found to be the best combination for ester‐directed bromocyclization of o ‐alkynylbenzoates 184 .…”
Section: In Situ Generation and Further Reactivity Of Gem‐dihalocarbomentioning
confidence: 99%
“…This strategy not only applicable for ester but also useful for aldehyde and ketone assisted reactions. Further, they reported the NBS promoted, an alternative strategy, for the synthesis of 1,2‐diketones 185 from alkyne 184 via dibromocarbonyl intermediate 184 a . Both of these protocols are very general to make broad substrate scope with good to excellent yields.…”
Section: In Situ Generation and Further Reactivity Of Gem‐dihalocarbomentioning
confidence: 99%
“…Considering our continuous interests in developing application of dual-functional substrates in organic synthesis, we were focused mainly on o -alkynylbenzoate chemistry with a wish to exploit diverse o -alkynylbenzoate-based transformations. Accordingly, a N -bromosuccinimide (NBS)/water-mediated diketonization of o -alkynylbenzoate was established by our group for the synthesis of benzil- o -carboxylates . Interestingly, the diketonization of o -alkynylbenzoate was ascribed to a neighboring-ester-participated 1,1-dibromohydration of alkyne.…”
mentioning
confidence: 99%